Lactobacillus plantarum CCFM1143 Alleviates Chronic Diarrhea via Inflammation Regulation and Gut Microbiota Modulation: A Double-Blind, Randomized, Placebo-Controlled Study - Yang, Bo; Yue, Yue; Chen, Yang; Ding, Mengfan; Li, Bowen; Wang, Linlin; Wang, Qun; Stanton, Catherine; Ross, R. Paul; Zhao, Jianxin; Zhang, Hao; Chen, Wei (Frontiers in Immunology, 2021)
Irritable bowel syndrome with diarrhea and functional diarrhea are both functional bowel disorders that cause chronic diarrhea. Chronic diarrhea is closely related to daily life and the psychological condition of diarrhea in patients, and probiotics can play a significant role in alleviating chronic diarrhea in some research. Lactobaccilus plantarum CCFM1143 can relieve diarrhea in mice caused by enterotoxigenic Escherichia coli (ETEC); however, its clinical effects remain unclear. This study aimed to assess the effects of CCFM1143 as a therapy for chronic diarrhea patients. Fifty-five patients with chronic diarrhea were randomly assigned into the probiotic group (n = 28) and the placebo group (n = 27), receiving the routine regimen with or without probiotics for 4 weeks, respectively. CCFM1143 can mitigate the apparent clinical symptoms and improve the health status and quality of life of patients. In addition, it could inhibit the increase in interleukin 6 (IL-6) and the decrease in motilin; modulate the short-chain fatty acids, especially acetic and propionic acids; and regulate the gut microbiota, particularly reducing the abundance of Bacteroides and Eggerthella and enriching the abundance of Akkermansia, Anaerostipes, and Terrisporobacter. In addition, treatment with probiotics showed clinical effectiveness in managing chronic diarrhea when compared with the placebo group. The findings could help to develop and further the application of probiotics for chronic diarrhea.